2002
DOI: 10.1176/appi.ajp.159.3.480
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-Controlled Trial of d-Cycloserine Added to Conventional Neuroleptics, Olanzapine, or Risperidone in Schizophrenia

Abstract: These data support the efficacy of the addition of 50 mg/day of D-cycloserine to treatment with conventional neuroleptics and suggest that therapeutic benefits may also be attained when D-cycloserine is added to olanzapine or risperidone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(64 citation statements)
references
References 11 publications
0
63
0
1
Order By: Relevance
“…Beneficial effects on negative symptoms were obtained in four trials (6,33,34,47), while four other studies (12,31,32,37) did not find a significant change. Two studies (36,46) with doses of 100 and 250 mg/day showed worsening of negative symptoms.…”
Section: D-cycloserine Added To Conventional Antipsychoticsmentioning
confidence: 78%
See 2 more Smart Citations
“…Beneficial effects on negative symptoms were obtained in four trials (6,33,34,47), while four other studies (12,31,32,37) did not find a significant change. Two studies (36,46) with doses of 100 and 250 mg/day showed worsening of negative symptoms.…”
Section: D-cycloserine Added To Conventional Antipsychoticsmentioning
confidence: 78%
“…Ten trials evaluated the addition of D-cycloserine to typical antipsychotics (6,12,(31)(32)(33)(34)36,37,46,47). Seven of them (6,12,31-34,47) did not find any significant change in positive symptoms and two (with higher dosages, namely 100 and 250 mg/day) reported worsening of positive symptoms (36,46).…”
Section: D-cycloserine Added To Conventional Antipsychoticsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported increased expression of G72 in prefrontal cortex [134]. The impressive replications of the association of G72 with the risk for schizophrenia is all the more intriguing, given recently replicated findings that (i) D-serine reduces negative symptoms, improves cognition and reduces positive symptoms in patients with chronic schizophrenia who are receiving concurrent typical antipsychotic medications [135,136] and (ii) that serum and cerebrospinal fluid levels of D-serine are reduced in schizophrenic subjects [40,131].…”
Section: Box 1 Schizophrenia Risk Genes That Affect Transmission At mentioning
confidence: 99%
“…Nevertheless, it has been observed clinically that these agents (glycine and D-serine) are effective in treatment of schizophrenia when combined with typical or newer atypical antipsychotics, 29 but may be less effective in the presence of clozapine. 30,31 Further, the partial antagonist D-cycloserine significantly improves symptoms of schizophrenia when combined with either typical 32,33 or newer atypical 34,35 antipsychotics, but paradoxically worsens symptoms when combined with clozapine. 36 …”
mentioning
confidence: 99%